Impact of Enteral Nutrition Within 24 Hours Versus Between 24 and 48 Hours in Patients With Severe Acute Pancreatitis: A Multicenter Retrospective Study. Issue 3 (March 2021) - Nakashima, Ikue; Horibe, Masayasu; Sanui, Masamitsu; Sasaki, Mitsuhito; Sawano, Hirotaka; Goto, Takashi; Ikeura, Tsukasa; Takeda, Tsuyoshi; Oda, Takuya; Yasuda, Hideto; Ogura, Yuki; Miyazaki, Dai; et al.
Abstract : Objectives: In patients with severe acute pancreatitis (SAP), early enteral nutrition (EN) is recommended by major clinical practice guidelines, but the exact timing for the initiation of EN is unknown. Methods: We conducted a post hoc analysis of the database for a multicenter (44 institutions) retrospective study of patients with SAP in Japan. The patients were classified into 3 groups according to the timing of EN initiation after the diagnosis of SAP: within 24 hours, between 24 and 48 hours, and more than 48 hours. The primary outcome was in-hospital mortality. Results: Of the 1094 study patients, 176, 120, and 798 patients started EN within 24 hours, between 24 and 48 hours, and more than 48 hours after SAP diagnosis, respectively. On multivariable analysis, hospital mortality was significantly better with EN within 48 hours than with more than 48 hours (adjusted odds ratio, 0.49; 95% confidence interval, 0.29–0.83; P < 0.001) but did not significantly differ between the groups with EN starting within 24 hours and between 24 and 48 hours ( P = 0.29). Conclusions: Enteral nutrition within 24 hours may not confer any additional benefit on clinical outcomes compared with EN between 24 and 48 hours.